Sodium Lactate Accelerates M2 Macrophage Polarization and Improves Cardiac Function after Myocardial Infarction in Mice - Jialiang Zhang; Fangyang Huang; Li Chen; Guoyong Li; Wenhua Lei; Jiahao Zhao; Yanbiao Liao; Yijian Li; Changming Li; Mao Chen (Cardiovascular Therapeutics)
Background. After myocardial infarction, anti-inflammatory macrophages perform key homeostatic functions that facilitate cardiac recovery and remodeling. Several studies have shown that lactate may serve as a modifier that influences phenotype of macrophage. However, the therapeutic role of sodium lactate in myocardial infarction (MI) is unclear. Methods. MI was established by permanent ligation of the left anterior descending coronary artery followed by injection of saline or sodium lactate. Cardiac function was assessed by echocardiography. The cardiac fibrosis area was assessed by Masson trichrome staining. Macrophage phenotype was detected via qPCR, flow cytometry, and immunofluorescence. Signaling proteins were measured by Western blotting. Results. Sodium lactate treatment following MI improved cardiac performance, enhanced anti-inflammatory macrophage proportion, reduced cardiac myocytes apoptosis, and increased neovascularization. Flow-cytometric analysis results reported that sodium lactate repressed the number of the IL-6+, IL-12+, and TNF-α+ macrophages among LPS-stimulated bone marrow-derived macrophages (BMDMs) and increased the mRNA levels of Arg-1, YM1, TGF-β, and IL-10. Mechanistic studies revealed that sodium lactate enhanced the expression of P-STAT3. Furthermore, a STAT3 inhibitor eliminated sodium lactate-mediated promotion macrophage polarization. Conclusion. Sodium lactate facilitates anti-inflammatory M2 macrophage polarization and protects against MI by regulating P-STAT3.